DETERMINATION OF POLYCYCLIC AROMATIC HYDROCARBONS IN SOIL SAMPLES USING ULTRASONIC PROBE AND SALT-ASSISTED LIQUID-LIQUID EXTRACTION COUPLED WITH HIGH-PERFORMANCE LIQUID CHROMATOGRAPHY - Rouhollah Heydari; Arezoo Shakarami; Massoud Kaykhaii (Journal of the Chilean Chemical Society, 2019)
Background: Polycyclic aromatic hydrocarbons (PAHs) are a class of chemicals which have 2 to 7 fused aromatic rings. It is demonstrated that even trace amounts of PAHs are carcinogens, mutagens, and teratogens which can lead to serious risk to the health of humans. According to these facts, determination of PAHs in environmental samples is essential. Methods: In this study, ultrasonic in combination with salt-assisted liquid-liquid extraction was used efficiently for the extraction of PAHs from soil and water samples. In order to evaluate the performance of the proposed method three PAHs, naphthalene, anthracene and pyrene were selected as model analytes. Influential parameters on the extraction efficiency of analytes such as extraction solvent and its volume, salting-out agent and its concentration, ultrasonic time, ultrasonic amplitude and pulse were investigated and optimized. Results: The optimum conditions were as follow; extracting solvent; tetrahydofuran, extracting solvent volume; 3 mL, salting-out agent; sodium acetate, salting-out agent concentration; 20 %w/v, ultrasonic time; 10 s, ultrasonic amplitude; 60% and ultrasonic pulse; 0.5 s. The limits of quantitation for pyrene, naphthalene and anthracene were 1.0, 1.0 and 0.7 ng g-1, respectively. Under the optimum conditions, obtained recoveries in different matrices were in the range of 80.0 to 100.0% with a relative standard deviation better than 7.5%. Conclusions: In the proposed method, after the UAE, sample was exposed to SALLE without need of solid residue removal from the sample. Therefore, extraction steps such as filtration and centrifuge were removed which lead to time saving.